Anarchism and Utopia - Giacomoni, Valeria (2022)
The text intends to clarify a little the relationship between anarchism and the concept of utopia. If the absence of States can be considered the maximum ideal of anarchism, there must be the need to decline the steps that could lead to the maximum "Utopia", that is, in a journey through literature and history.